Nickel‐Catalyzed Difluoroalkylation of (Hetero)aryl Bromides with Unactivated 1‐Bromo‐1, 1‐difluoroalkanes1. Issue 11 (19th September 2018) - He, Xu; Gao, Xing; Zhang, Xingang
Abstract: Although extensive efforts on fluoroalkylations have been made over the past decade, new and efficient methods to incorporate fluorinated groups into organic molecules remain highly desirable. Herein, we report an efficient method for catalytic synthesis of difluoroalkylated (hetero)arenes through nickel‐catalyzed reaction between readily accessible (hetero)aryl bromides and unactivated 1‐bromo‐1, 1‐difluoroalkanes. The reaction exhibits high functional group tolerance and broad substrate scope, providing a cost‐efficient and straightforward route for applications in medicinal chemistry. Abstract : A title reaction has been developed (see the Scheme). The reaction enables the difluoroalkylations of a variety of (hetero)arylbromides with unactivated difluoroalkylbromides with high efficiency and excellent functional group tolerance. The feature of this approach is the synthetic simplicity without preformation of arylmetals, thus providing a facile route for applications in medicinal chemistry.